Synthesis of hydroxyapatite from cockle shell wastes - Siti Hajar, Saharudin; Jun Haslinda, Haji Shariffuddin; Aqeela, Ismail (Universiti Malaysia Pahang, 2018)
Cockle shell wastes are abundant and easily available. It rich in calcium carbonate (CaCO3) that can be converted into hydroxyapatite. HAP has numerous benefits especially in biomedical applications. The overall objective of this study is to determine the effect of reaction time on producing HAP derived from cockle (Anadara granosa) shells waste. There are two reaction times used in this study which are 3 h and 5 h. The processes involved in synthesizing the HAP were pre-treatment of the cockle shells, formation of CaCO3 in aragonite form, calcination of the CaCO3 to form CaO, production of Ca(OH)2 and finally reaction of the Ca(OH)2 solution with the phosphate source to obtain HAP. All samples have undergone physicochemical analyses to determine their crystallinity, purity, functional group, surface morphology and elemental compounds using X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM) and Electron Dispersive X-ray Analysis (EDX). This study found that 5 h reaction time produced powder is better HAP compared to the 3 h powder. Overall, this study proved that reaction time plays a vital role in the quality of producing HAP. Longer the reaction time has enhanced the quality of the HAP formed.